Endangered Compound Prosody in Kansai Japanese - Angeles, Andrew (Brill, 2024)
This book examines the diverse prosody of compound nouns in Kansai Japanese, with a special focus on a class of compounds with particularly variable prosody, whose unique prosody is potentially endangered due to their structure and influence from Tokyo Japanese. These compounds serve as important evidence for recursion in prosodic structure in theories of the syntax-prosody interface, as they simultaneously resemble not only other compound words but also non-compound phrases, making them valuable test cases for compound prosodic structure. This book discusses potential reasons for these compounds' prosodic variabilty and what may condition their unique prosody, based on results from novel fieldwork. A unified account of compound prosody in Kansai and three other Japanese dialects is also presented.